Cloning of the opsin genes present in Bothrops atrox (Viperidae) retina - Stacey Solís, Micaela (2017)
The visual system of vertebrates has evolved over millions of years to adapt to nocturnal or diurnal habits as well as different environments where varying spectral range and intensity of light are present. Although much is known about the visual system of vertebrates in general, studies about reptiles, and snakes in particular, are scarce. Reptiles display great diversity regarding their retinal structure, and different types of retinas exist (pure cone, mostly rod or duplex retina); however, the same five opsins are found in all of these animals. Because of their nocturnal and fossorial origins, snakes only have three of these visual opsins, namely: RH1 (rhodopsin-like 1) present in rods, LWS (long10 wavelength sensitive), and SWS1 (short-wavelength sensitive 1) that are present in cones. The study of snakes´ opsins has been largely ignored in the past; however, its importance has become clear within the past few years, and studies which reconsider Wall´s transmutation theory, proposed back in 1934, have emerged. In this study, we cloned the full length of RH1 and LWS opsins, as well of a part of the SWS1 opsin present in Bothrops atrox and have used these sequences to predict the Maximal absorbance (λmax) for each protein. This is the first report focusing on viper opsins; we report the first full length sequences available for opsins of this family, which has been poorly studied so far.